2022
DOI: 10.3389/fnmol.2022.1004221
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal noncoding RNAs in central nervous system diseases: biological functions and potential clinical applications

Abstract: Central nervous system (CNS) disease is a general term for a series of complex and diverse diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple sclerosis (MS), CNS tumors, stroke, epilepsy, and amyotrophic lateral sclerosis (ALS). Interneuron and neuron-glia cells communicate with each other through their homeostatic microenvironment. Exosomes in the microenvironment have crucial impacts on interneuron and neuron-glia cells by transferring their contents, such as proteins, lipids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 207 publications
0
18
0
1
Order By: Relevance
“…Numerous RNAs can be employed as biomarkers for the diagnosis, management, and prognosis of AD. Wang Z. Y. et al (2022) summarized various functions of exosomal noncoding RNAs in AD in a review published in Frontiers in molecular neuroscience in 2022 and found that different RNAs have different roles in affecting the elimination and accumulation of Aβ, APP and tau, which can be used as good pathological modulators and biomarkers. MiRNA has the largest number of non-coding RNA subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous RNAs can be employed as biomarkers for the diagnosis, management, and prognosis of AD. Wang Z. Y. et al (2022) summarized various functions of exosomal noncoding RNAs in AD in a review published in Frontiers in molecular neuroscience in 2022 and found that different RNAs have different roles in affecting the elimination and accumulation of Aβ, APP and tau, which can be used as good pathological modulators and biomarkers. MiRNA has the largest number of non-coding RNA subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The development of reliable for diagnosing early neurodegeneration and its molecular signaling will be pivotal for increased efficiency of therapies. Some studies evaluated targeting and transcriptionally repressing ncRNAs by silencing ncRNAs and RNA interference to inhibit ncRNAs expression in neurodegenerative disorders (Wang et al 2022 ; Zhang et al 2021b ). Moreover, CRISPRs could be applied to delete miRNAs/lncRNAs (Ho et al 2015 ) and assess the consequences for therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…While a search for circRNA in MS yielded 16 review papers, none of them discussed the role of circRNA in MS as comprehensively as this review. Some of these papers barely mentioned circRNA, 64,[86][87][88][89][90][91][92] while others focused on other types of ncRNAs such as miRNA and LncRNA. 93,94 A few papers discussed the role of circRNA in other types of diseases but did not mention MS. [95][96][97][98] The lack of comprehensive discussion on the role of circRNA in MS and other diseases may be attributed to the limited understanding of this molecule.…”
Section: Discussionmentioning
confidence: 99%